A Meta-Analysis of the Cognitive, Affective, and Interpersonal Outcomes of Flipped Classrooms in Higher Education - Hwan Young Jang; Hye Jeong Kim (MDPI AG, 2020)
This paper aims to quantify the effects of flipped classrooms in higher education by reviewing 43 empirical studies of students' cognitive, affective, and interpersonal outcomes. The innovative pedagogy of a flipped classroom in higher education fosters a sustainable, interactive, and student-centered learning environment (as opposed to the traditional lecture style, in which there is little room for interaction). This study's results show the positive effects of flipped classrooms and highlight the improvement in students' educational outcomes between 2012 and 2017. Overall, effect sizes were medium-effect size (ES) = 0.35, 95% confidence interval (CI) = 0.24 to 0.47-across three outcome domains using a random effects model. In the outcomes, affective (ES = 0.59), interpersonal (ES = 0.53), and cognitive (ES = 0.24) domains were of a higher order than the effect sizes. However, the results indicated that flipped classrooms benefitted students studying chemistry, engineering, mathematics, and physics less than they did students studying other subjects.